2016
DOI: 10.3727/215517916x693366
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Mesenchymal Stem Cell Transplantation in Dogs with Keratoconjunctivitis Sicca

Abstract: Keratoconjunctivitis sicca (KCS) is a dysfunction in tear production associated with clinical signs, which include conjunctival hyperemia, ocular discharge, discomfort, pain, and, eventually, corneal vascularization and pigmentation. Immunosuppressive drugs are routinely administrated for long periods to treat KCS but with side effects and limited results. Evaluation of the clinical benefits of intralacrimal transplantation of allogeneic mesenchymal stem cells (MSCs) in dogs with mild-moderate and severe KCS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 55 publications
1
38
0
9
Order By: Relevance
“…In dogs, the presence of HSCs have been observed mostly in bone marrow and umbilical cord blood, being used in cell therapy for neoplasia, hematological, metabolic, and immunological diseases (Bruno et al 2009, Nakage et al 2009, Ryu et al 2012, Bittencourt et al 2016, Stolfi et al 2016.…”
Section: Hematopoietic Stem Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…In dogs, the presence of HSCs have been observed mostly in bone marrow and umbilical cord blood, being used in cell therapy for neoplasia, hematological, metabolic, and immunological diseases (Bruno et al 2009, Nakage et al 2009, Ryu et al 2012, Bittencourt et al 2016, Stolfi et al 2016.…”
Section: Hematopoietic Stem Cellsmentioning
confidence: 99%
“…Additionally, several studies demonstrated, the regenerative function of these cells in damaged tissues (Narazaki & Cristante 2011, Ryu et al 2012, Bittencourt et al 2016, Stolfi et al 2016.…”
Section: Topic Of General Interestmentioning
confidence: 99%
See 3 more Smart Citations